2006
DOI: 10.1097/01.inf.0000207485.39112.bf
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Outpatient Bacteremia in 3- to 36-Month-Old Children After the Introduction of the Heptavalent-Conjugated Pneumococcal Vaccine

Abstract: In the United States, routine vaccinations with Haemophilus influenzae type b and S. pneumoniae vaccines have made bacteremia in the previously healthy toddler a rare event. As the incidence of pneumococcal bacteremia has decreased, E. coli, Salmonella spp. and Staphylococcus aureus have increased in relative importance. The use of the white blood cell count alone to guide the empiric use of antibiotics is not indicated. New guidelines are needed to approach the previously healthy febrile toddler in the outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
109
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(139 citation statements)
references
References 25 publications
21
109
1
8
Order By: Relevance
“…Although we have no concrete explanation for this fi nding, it may refl ect decreasing concern about bacteremia in general because rou tine vaccination against pneumococcus began in 2000 in the United States. 11,18,19 This hypothesis is supported by our demonstration that the decrease was more pronounced in infants aged ≥4 months. The reported prevalence from previous studies of bacteremic UTIs in children is variable.…”
Section: Discussionsupporting
confidence: 77%
“…Although we have no concrete explanation for this fi nding, it may refl ect decreasing concern about bacteremia in general because rou tine vaccination against pneumococcus began in 2000 in the United States. 11,18,19 This hypothesis is supported by our demonstration that the decrease was more pronounced in infants aged ≥4 months. The reported prevalence from previous studies of bacteremic UTIs in children is variable.…”
Section: Discussionsupporting
confidence: 77%
“…This trend was observed for the proportion of bacteraemia caused by Staph. aureus in young children after vaccination (Herz et al, 2006). Considering our results, these previous results support the suggestion that nasopharynx flora modification such as the elimination of Strep.…”
Section: Association Between Colonization Of the Four Bacteriasupporting
confidence: 80%
“…Previous studies indicated that white blood cell count is an imperfect tool for distinguishing between viral and bacterial infection, a distinction often used to determine whether to treat the patient with antibiotics (21,22). We compared classification based on transcriptional profiles with classification based on white blood cell count using a cutoff of 15,000/mm 3 as recommended by the American Academy of Pediatrics in their guideline for the management of febrile young children 0-36 mo of age (23).…”
Section: Transcriptional Profile Was Superior To Traditional White Blmentioning
confidence: 99%